The relationship between pelvic floor functions and vaginal microbiota in 6–8 weeks postpartum women - Zhang, Yakun; Yang, He; Lin, Li; Yang, Wenlan; Xiong, Guangwu; Gao, Guolan (Frontiers in Microbiology, 2022)
The impairment of pelvic floor muscle functions and Lactobacillus-deficient vaginal microbiota are common in postpartum women. However, few studies have explored the correlation between pelvic floor muscle functions and vaginal microbiota. Given this research gap, our study aims to investigate any potential association between pelvic floor muscle functions and vaginal microbiota of postpartum women (6-8 weeks after childbirth). 230 participants were enrolled who were required postpartum pelvic floor functions examination at Peking University International Hospital from December 2021 to April 2022. The collected questionnaire information included progestational weight, body mass index (BMI), weight gain during pregnancy, neonatal weight, delivery type, multiparity, postpartum time and urinary incontinence (UI). A total of 187 samples of vaginal secretions were collected and the vaginal microbiota was detected by 16S rRNA sequence analysis. Finally, 183 samples were analyzed in the trial. All individuals were divided into two groups according to the results of pelvic floor muscle assessment to explore the difference between the incidence of postpartum urinary incontinence and vaginal microbiota. We found that the prevalence of UI was higher in the group with weekend pelvic floor muscles. Vaginal delivery, overweight, age, neonatal weight and weight gain during pregnancy were all risk factors for postpartum urinary incontinence. The vaginal microbiome was no longer Lactobacillus dominant of most postpartum women (91.8%), while the diversity of microbiota increased. The Lactobacillus-deficient community, commonly labeled as community state type (CST) IV was sub-divided into four communities. The abundance of vaginal Lactobacillus decreased in the group with compromised pelvic muscle functions, while the species richness and diversity increased significantly. In conclusion, the decreased pelvic floor muscle functions of postpartum women 6-8 weeks after delivery may disrupt the balance of vaginal microbiota and the restoration of pelvic floor functions may contribute to a healthy and balanced vaginal microbiota.